PROXY SERVER ON INSTALLING MICROSOFT WINDOWS SERVER 2003 - Rakenurdi Lubis; Indrianto Indrianto, SKom, MT (Jurnal Sistem Komputer, 2006)
It is a fact that the size of internal data paths in the network are generally wider than the data point to the Internet. Not to mention the expensive installation and use of data paths to the Internet is fast enough and wide as needed. It has long been a proxy used technique for dealing with problems in the data path. Although not constitute the best and latest, but the proxies are able to leverage the use of the available data paths. Even though already have a data path width to the Internet, many networks use a proxy to get the efficiency of the data path. In the proxy technique, one or more servers are used as intermediaries to the Internet and manage the cache for web objects obtained from the Internet. As an intermediate point is a proxy server that takes the user desired web object from the source. In addition to retrieve web objects from the source, the proxy server is also in charge of creating, storing and managing the copy of the object. At another time, if the desired web object returned by the user, then copy it caches web objects tersebutlah provided by the proxy server. Because the objects obtained by web users more often than the cache proxy server instead of the original source, hence the use of data paths to the Internet to a minimum. In addition access times are obtained by the user becomes smaller because of the relationship that occurs within an internal data path network / local faster than using the path to the Internet. In order for a server can be a proxy server then needs to be attached to him an application proxy services. There bemacam-kind application proxy services on the market that is suitable for various operating systems. In addition some applications also have a good firewall services mengikutertakan proxy service in it.